The perimeter of a right triangle is 24 cm. Three times the length of the longer side minus two times the length of the shorter side exceeds hypotenuse by 2 cm.what are the lengths of all three sides??state method too.

Whenever you have \(n\) equations and \(n\) variables, just go on substituting from one to other and finally you reach 1 variable which leads to all others.

Our current Example is,

(i) \(a+b+c=24\); (ii) \(3a-2b=c+2\); (iii) \(a^2+b^2=c^2\).

Use \(c=24-(a+b)\). So now you only have 2 equations and 2 variables.

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestIf someone understood the answer then please answer me writing it step by step upto the end in 12hrs plssssss.its urgent

Log in to reply

Done . Next time, give a

reasonableheading to your note.Log in to reply

Thanks very much...:-)

Log in to reply

\(\triangle ABC\), let it be right angled at \(B\). (Hypotenuse \(AC\)).

Let \(AB\leq BC\).

From \(1^{st}\) statement, \(AB+BC+CA=24\)

From \(2^{nd}\) statement, \(3\times BC -2\times AB = AC+2\)

By Pythagoras' theorem \(AC^2=AB^2+BC^2\).

Now it's simply 3 equations and 3 variables, solving simultaneously gives

\(AC=10 , BC=8, AB=6\)

Great Challenge (?).... I'm a moderator, can edit titles of only problems, can't edit the titles of Notes...Log in to reply

Please answer writing each step to the end..plse help me!!!

Log in to reply

As fast as possiblePlease help me

Log in to reply

Can u please write the whole calculation so I can understand because up to here I also did easily

Log in to reply

Whenever you have \(n\) equations and \(n\) variables, just go on substituting from one to other and finally you reach 1 variable which leads to all others.

Our current Example is,

(i) \(a+b+c=24\); (ii) \(3a-2b=c+2\); (iii) \(a^2+b^2=c^2\).

Use \(c=24-(a+b)\). So now you only have 2 equations and 2 variables.

(i) \(3a-2b=24-(a+b)+2\); (ii)\(a^2+b^2 = (24-a-b)^2\)

i.e. \(4a-b=26\) , \(576+2ab-48a-48b=0\) i.e. \(24a+24b-ab=288\)

Now do substitution \(a = \dfrac{26+b}{4}\)

\(24\biggl(\dfrac{26+b}{4}\biggr) +24b -\biggl(\dfrac{26+b}{4}\biggr) b = 288\\ \therefore 156+30b-\dfrac{b^2+26b}{4} =288\)

This is a quadratic in \(b\), and has positive root \(6\).

Put \(b\) value in \(a=\dfrac{26+b}{4} = \dfrac{26+6}{4} = 8\)

And finally, \(c=10\)

Sides \(6,8,10\).

Log in to reply